AKTIVITAS HARIAN DAN FREKUENSI BEGGING BEHAVIOUR DARI ELANG BONDOL (Haliastur indus) SITAAN DI PUSAT PENYELAMATAN SATWA, TABANAN, BALI - Widiyavedanta, Gde Oka; Yuni, Luh Putu Eswaryanti Kusuma; Ginantra, I Ketut (SIMBIOSIS, 2021)
Brahminy kite ( Haliastur indus ) is one of bird of prey species that occupy position as top predator. Many brahminy kite was captured and was kept as pet which caused those birds lose their ability to hunt as a result of being caged for too long and for not to be trained to hunt. In Bali Wildlife Rescue Centre, the confiscated brahminy kite showed begging behavior in which the birds “whine” every time a human approach. This kind of behaviour affect their readiness to be released in the wild. The purpose of this study was to determine the daily activity and the frequency of begging behaviour of confiscated brahminy kite in Bali Wildlife Rescue Centre. This study was conducted in January 2020. This study found that the brahminy kite at the Bali Wildlife Rescue Centre spent the most of their time for perching. The second highest activity was preening, whereas the least activities were feeding and moving.  The highest percentage to beg in brahminy kite was recorded in the morning, whereas the lowest percentage was in the midday. The results of this study indicate that the confiscated brahminy kite at the Bali Wildlife Rescue Centre still needs more time to be rehabilitated prior released ack into the wild.